Penyelesaian Sengketa Batas Daerah Menggunakan Pendekatan Regulasi - Saru Arifin (Jurnal Hukum IUS QUIA IUSTUM, 2016)
One of the increasing trends in the era of regional autonomy is the regional extension both at the provincial level and at district/city level. However, such situation in some cases has emerged some new problems, such as: social conflict, conflict on natural resources and conflict in the regional boundaries. This study examines the problems; first, what factors are causing the dispute on the boundaries in the extension of new autonomous region? Second, how is the pattern of the settlement of boundary dispute provided in the Indonesian legal system? Third, what is the role of the Government in solving the boundary dispute? This is a juridical-empirical research. The study concluded that: First, the boundary dispute has been triggered by the area extension process not requiring the border as a legal requirement in the area expansion. The requirements fulfilled were more technical, physical and political. Second, the pattern of the boundary dispute resolution generally is through two ways: the non-legal border dispute resolution, and legal settlement. In non-legal resolution, it was mediated by MOHA and Governors; while, in the legal dispute resolution it reached through a judicial review to the Supreme Court or the Constitutional Court. Third, in the dispute of area border, the government's role was the facilitator in accordance with the level of its dispute case.